3D Printed Chiral Cellular Solids with Amplified Auxetic Effects Due to Elevated Internal Rotation1 . Issue 2 (25th October 2016) - Jiang, Yunyao; Li, Yaning
Abstract : For the first time, the concept of amplifying chirality‐induced auxetic effect via elevating internal rotation efficiency is proposed. Based on this concept, new chiral cellular solids with center cores and softer hinges are designed and fabricated via multi‐material 3D printing. The new designs are proved via mechanical experiments and finite element (FE) simulations to have robust and amplified auxetic effects under large deformation. A linear relationship between the internal rotation efficiency and the Poisson's ratio is discovered. To bridge the conceptual model and the real cellular solids, systematic FE simulations are performed and provided guidelines to design this new family of chiral cellular solids with robust auxetic effects via jointly tailoring geometry and material composition. Abstract : For the first time, the concept of amplifying chirality‐induced auxetic effect via elevating internal rotation efficiency is proposed and proved via multi‐material 3D printing, mechanical experiments, and finite element (FE) simulations. A linear relationship between the internal rotation efficiency and the Poisson's ratio is discovered. This study provides guidelines to design new chiral cellular solids with robust auxetic effects under large deformation.